Implementasi Kebijakan Kendali Mutu dan Kendali Biaya Dalam Era Jaminan Kesehatan - shelvy haria roza; Kamal Kasra; Annisa Rahmayona (VISIKES: Jurnal Kesehatan Masyarakat, 2022)
The coverage of the National Health Insurance (JKN) participation continues to increase but participant satisfaction with health services decreases. Quality control and cost control policies are efforts to improve the quality and satisfaction of JKN participants. This study aims to analyze the implementation of Quality Control and Cost Control (KMKB) policies in Padang City  This research was conducted at BPJS Health Offices, Hospitals and Health Centers in Padang City in 2019. This study used quantitative and qualitative methods. Quantitative data in the form of secondary data from participant satisfaction index reports and health facilities were analyzed with descriptive statistics. Qualitative research is carried out with a systems approach, namely the components of input, process, and output. . Collecting qualitative data with in-depth interviews and document review. Research informants were determined by purposive sampling with a total of 9 informants. Qualitative data analysis by triangulation of sources and methods. The results showed that the satisfaction index of participants and health service providers in 2016-2019 had increased. although it has not yet reached the target according to the JKN target map. The average satisfaction of JKN-KIS participants reached 80.1% and the satisfaction rate of JKN-KIS providers was 79.15%. Quality and cost control has been implemented at the advanced referral health facility (FKRTL) level in Padang City. The input components found that not all hospitals have a KMKB team but have carried out and carried out quality and cost control activities. The output component has been executed but the work achievement cannot be known because it cannot be measured. Quality and cost control efforts have been carried out and implemented, although not all Padang City FKRTLs have formed TKMKB. There is an increase in participant and provider satisfaction after the KMKB policy is implemented.